Identifying Strategies for Implementing Lean Management in Education - moharramali hashemi; Jahangir Yari Haj Atalou; Sadegh Maleki Avarsin (Allameh Tabataba'i University Press, 2022)
The purpose of this study was to identify strategies for implementing lean management in education. A qualitative research approach was used. The research field included all professors of management and educational sciences of Iranian universities. In-depth interviews were conducted with 15 experts to identify strategies for implementing lean management in education. To ensure the validity of the instrument during the research, the review of participating experts as well as the supervision of three non-participating professors was used. The participants' repeated review method was used to ensure the reliability of the data. In the open coding stage, 738 conceptual propositions were identified and by combining them, 20 pivotal codes were obtained. In the selective coding stage, six re-engineering codes in education economics, professional selection, motivation, effective measures, specific institutions and needs assessment as implementation strategies lean management was identified in education. Given the benefits of lean management in various dimensions, it is necessary to start by adopting effective guidelines for lean implementation in education.